СПОСІБ ПОКРАЩЕННЯ ЯКОСТІ СТРУМУ СИСТЕМИ МЕРЕЖА - ТИРИСТОРНИЙ КОМПЕНСАТОР РЕАКТИВНОЇ ПОТУЖНОСТІ - Чиженко, О.І.; Трач, І.В. (Інститут електродинаміки Національної академії наук України, 2017)
Method of smooth controlling  the reactive power  in the electrical network  using a thyristor reactive power compensator is proposed.  Smooth control is carried out under a load by switching taps inductive reactor coils. Significant improvement in the quality of the input current is accomplished by reducing higher harmonics therein levels. Referenses 3, figures 4, tables 2.